A CLOSE POSITIVE ASSOCIATION BETWEEN OBESITY AND BLOOD PRESSURE IN RATS - Yusni, Yusni; Yusuf, Hanifah (Universitas Syiah Kuala, 2022)
The purpose of this study was to analyze how the effect of each increase in Body Mass Index (BMI) on the increase in blood pressure (BP). The research design was a laboratory experiment with 52 non-obese and obese rats as subjects (non-obese, n=14 and obese, n=38). Rats were induced obesity using a high-fat diet for four weeks. BMI used is based on the Lee Index with obesity indicators if 300 g/cm. Data analysis using independent sample t-test, simple linear regression test, and Pearson correlation test; (p0.05). The results: BP in non-obese rats was lower than obese rats (89.007.38 vs 190.114.42; p=0.001*), BMI was positively associated with BP (p=0.001*); an increase in BMI will increase BP (p=0.001*), there is a strong correlation between BMI and BP (r=0.977; p=0.001*). The regression equation (Y = 707.42 + 2.75 X) indicates that every 1 g/cm increase in BMI will be followed by an increase in BP of 2.75 mmHg. The analysis of R-square = 0.942 shows that the accuracy of the linear equation model is 94.2%. In conclusion, BMI has a strong positive correlation with BP, an increase in BMI will increase BP; obesity induces high blood pressure in rats.